Short Communication: Roosting behavior of Wintering Barn Swallow (Hirundo rustica) in Peninsular Malaysia - Nor Adibah Ismail; ABDILLAH BAGIR ABDUL KADIR AL JUFRI; UMMI NUR SYAFIQAH DAUD; SHUKOR MD. NOR; MOHAMMAD SAIFUL MANSOR (Society for Indonesian Biodiversity, 2020)
Abstract. Ismail NA, Jufri ABAK, Daud UNS, Nor SM, Mansor MS. 2020. Short Communication: Roosting behavior of Wintering Barn Swallow (Hirundo rustica) in Peninsular Malaysia. Biodiversitas 21: 661-665. The East Asian Barn Swallow Hirundo rustica gutturalis primarily breeds in China, Japan, and Korea, typically migrates to Southeast Asia during winter, including Malaysia. To date, knowledge regarding population of Barn Swallow are limited to their breeding grounds and other subspecies (e.g., European Barn Swallow Hirundo rustica rustica). A previous study on Barn Swallow wintering in Malaysia was conducted approximately 50 years ago and mainly focused on population dynamics. The objective of the present study was to investigate the roosting behavior of wintering Barn Swallows in a major roosting site, Bentong, central Peninsular Malaysia, from October 2018 to March 2019. Scan sampling at 5-min intervals was used to examine the roosting behavior of the swallows perching on service wires (i.e., electricity and telephone wires). We found that the swallows began to roost an average of 10 minutes after sunset and slept 55 minutes later. However, cloudy and rainy weather significantly affects swallow roosting period, leading them to perch earlier, 5 minutes before sunset. The pattern of roosting behavior was somewhat similar throughout the migration season, except in the early migration season (October), which was likely inconsistent due to their early adaptation to the town environment. Behavioral scan sampling revealed that swallows spend most of the time motionless, followed by preening. However, anthropogenic disturbances disrupt their behavior and sleep time. We also noted that this communally roosting bird behaved gregariously on wires, particularly at sites illuminated by light, which is likely an anti-predator mechanism.